Microtubule inhibitor, SP-6-27 inhibits angiogenesis and induces apoptosis in ovarian cancer cells - Kulshrestha, Arpita (Oncotarget, 2017)
In ovarian cancer (OVCA), treatment failure due to chemo-resistance is a serious challenge. It is therefore critical to identify new therapies that are effective against resistant tumors and have reduced side effects. We recently identified 4-H-chromenes as tubulin depolymerizing agents that bind to colchicine site of beta-tubulin. Here, we screened a chemical library of substituted 4-H-chromenes and identified SP-6-27 to exhibit most potent anti-proliferative activity towards a panel of human cisplatin sensitive and resistant OVCA cell lines with 50% inhibitory concentration (IC(50); mean ± SD) ranging from 0.10 ± 0.01 to 0.84 ± 0.20 μM. SP-6-27 exhibited minimum cytotoxicity to normal ovarian epithelia. A pronounced decrease in microtubule density as well as G2/M cell cycle arrest was observed in SP-6-27 treated cisplatin sensitive/resistant OVCA cells. The molecular mechanism of SP-6-27 induced cell death revealed modulation in cell-cycle regulation by upregulation of growth arrest and DNA damage inducible alpha transcripts (GADD45). An enhanced intrinsic apoptosis was observed in OVCA cells through upregulation of Bax, Apaf-1, caspase-6, -9, and caspase-3. In vitro wound healing assay revealed reduced OVCA cell migration upon SP-6-27 treatment. Additionally, SP-6-27 and cisplatin combinatorial treatment showed enhanced cytotoxicity in chemo-sensitive/resistant OVCA cells. Besides effect on cancer cells, SP-6-27 further restrained angiogenesis by inhibiting capillary tube formation by human umbilical vein endothelial cells (HUVEC). Together, these findings show that the chromene analog SP-6-27 is a novel chemotherapeutic agent that offers important advantages for the treatment of ovarian cancer.